ANALISIS KOORDINASI RELAY ARUS LEBIH (OCR) DAN RECLOSER PADA SISTEM EKSISTING PENYULANG BUKIT JATI - Wijana, Wayan; Wijaya, I Ketut; Mataram, I Made (Jurnal SPEKTRUM; Vol 5 No 2 (2018): Jurnal SPEKTRUM, 2018)
Protection systems play an important role to maintain the reliability of distribution line. Over current relay (OCR) is one of the equipments used as a protection line of 20 kV distribution. Feeder of Bukit Jati is equipped over current protection relay equipment installed in Recloser of Banda and relay in the substation feeder. Based on the data of PT. PLN (Persero) APD Bali, there are 5 time-short circuit disorders which one of them tripped the Bukit Jati feeder. Problems over current relay coordination failures can be overcome by analyzing the coordination of protection systems in the feeder of Bukit Jati. The analysis was done by recalculating the over current relay setting and create the coordination curve of the existing setting and compared it with the coordination curve setting according to the calculation result. The results of the calculation of instant recloser recycling settings obtained by 1.246 A with time multiple setting (Tms) of 0.11 while the value of the instant current setting of the feeder of 2.992 A with Tms of 0.38. Based on the simulation result using ETAP program, it is known that over current relay coordination has worked according to the protection zone when the noise occurrence behind the recloser bus did not result in a trip feeder.